The Legal Protection Against Children Through A Restorative Justice Approach - Bimo Bayu Aji Kiswanto; Anis Mashdurohatun (Law Development Journal, 2021)
The purpose of this research is to save the future of child offenders who are in conflict with the law. This research is expected to provide a better understanding of the importance of handling child criminal cases outside the formal legal channels to ensure and respect the dignity of the child, the best interests of the child by paying attention to justice for victims Currently, the handling of juvenile criminal cases through Restorative Justice is regulated in Article 52 of Act No. 11 of 2012 concerning the Juvenile Criminal Justice System. The research approach method used is Normative research methods, namely research on criminal law norms contained in Indonesian criminal legislation. The conclusion of this study is that society is expected to be more understanding if children are legal subjects and national assets, as part of the younger generation, children play a very strategic role as the next generation of a nation. In the context of Indonesia, children are the successors to the ideals of a nation's struggle. This strategic role has been recognized by the international community to give birth to a convention which essentially emphasizes the position of the child. A child by nature still has reasoning power that is not yet good enough to distinguish between good and bad things. Crimes committed by children in general are a process of imitating or being influenced by adults.